Pengaruh Reward dan Punishment terhadap Prestasi Kerja Karyawan PT.Senteral Inti Gas Medan - Rahmat Hidayat Harahap (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2021)
PT.Senteral Inti Gas is a company engaged in the field of gas distributors. Problem that occur in the company is: a decrease in employee work performance which is characterized by frequent errors in work, employee attendance rates began to decline and the emergence of procrastination work. The population in this study were all employees in the company of 67 people. The sample is taken by a saturated sampling technique in which all members of the population are used as samples. Thus the sample in this study amounted to 67 people. The simultaneous hypothesis test results show that reward and punishment have an influence on the work performance of employees of PT.Senteral Inti Gas Medan. The results of the partial hypothesis test show that the reward variable has a more dominant influence on the work performance of PT .enteral Inti Gas Medan employees compared to the punishment variable.